Polymyalgia rheumatica-like syndrome from checkpoint inhibitor therapy: case series and systematic review of the literature. Issue 1 (25th April 2019) - Calabrese, Cassandra; Cappelli, Laura C; Kostine, Marie; Kirchner, Elizabeth; Braaten, Tawnie; Calabrese, Leonard
Abstract : Objective: To assess whether the polymyalgia rheumatica (PMR)-like syndrome reported as an immune related adverse event (irAE) from checkpoint inhibitor therapy is consistent with the 2012 European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) provisional criteria for PMR. Methods: The cases were derived from two sources. Group 1 represents reported cases from three contributing centres. Group 2 was derived from a systematic review of the literature searching for all cases reported as PMR or PMR-like illness associated with checkpoint inhibitor therapy. Cases were assessed for the quality of reporting and then analysed to determine whether they fulfilled the 2012 EULAR/ACR provisional criteria for PMR. Results: A total of 49 patients were included for analysis. Among the entire group, 37 (75%) were designated 'complete' indicating that they had sufficient data to reliably apply the 2012 EULAR/ACR criteria. 28 (75%) cases fulfilled complete criteria for PMR. A number of cases also demonstrated some clinical features unusual for idiopathic PMR. Conclusion: This study suggests a high proportion of reported cases of checkpoint inhibitor-related PMR fulfil preliminary criteria for PMR, yet in one quarter clinical details were incomplete making verification problematic. Furthermore, in the absence of a gold standard for the diagnosis of PMR, the relationship of checkpoint inhibitor-related PMR to the idiopathic form remains unclear.